Anesthetic efficacy and safety of ropivacaine 0.75% versus bupivacaine 0.5% for spinal anesthesia in patients undergoing lower limb orthopedic surgery - Pratiti J Gohil,; Pankti Panchal,; Gauri M. Panjabi,; Jinal J. Gohil,; Ushma H. Thakar,; Raghav R. Rathi, (Asian Journal of Medical Sciences, 2023)
Background: Ropivacaine, a new amino-amide local anesthetic agent, is similar in chemical structure to bupivacaine. The low solubility of ropivacaine leads to greater sensory-motor differentiation by blocking sensory nerve fiber more readily than motor nervefibers. Early recovery of motor function is associated with decreased incidence of venous thromboembolism and early mobilization. Aims and Objectives: The present study aimed to compare the anesthetic efficacy and safety of hyperbaric ropivacaine 0.75% with hyperbaric bupivacaine 0.5% in spinal anesthesia in patients undergoing lower limb orthopedic surgery. Materials and Methods: A total of 60 patients aged between 18 and 60 years of either sex, ASA I and II, undergoing elective lower limb orthopedic surgery were randomly divided into two groups, ropivacaine (R) and bupivacaine (B) group. Group R received 3 mL of 0.75% hyperbaric ropivacaine and group B received 3 mL 0.5% hyperbaric bupivacaine intrathecally. The efficacy in terms of onset and duration of anesthesia, quality of anesthesia, and hemodynamic and safety in terms of complications were noted. Results: Group R produced faster onset of sensory block (ropivacaine 2.6±0.53 min; bupivacaine 3±0.56 min; P<0.006) and the mean duration of sensory block was significantly lesser compared to Group B (Ropivacaine 121.16±7.73 min; Bupivacaine 180.34±11.56 min; P<0.0001). Patients in Group R has significantly more rapid recovery of a motor blockade than Group B (ropivacaine 149.5±8.64 min; bupivacaine 210.17±13.19 min; P<0.0001). Conclusion: Hyperbaric ropivacaine 0.75% was found to be a comparable alternative to hyperbaric bupivacaine 0.5% in patients undergoing lower limb orthopedic surgery.